Pemberdayaan Hukum Masyarakat Talang Kawo Melalui Pemahaman Perjanjian Kredit Kendaraan Bermotor Dengan Jaminan Fidusia - Uli Kurniati Siregar, Ade; Apriadi Bahri, Rizki; Fathullah Saputra, Dipo; Apdillah, Dedek (PT. Meja Ilmiah Publikasi, 2025)
The low legal literacy of the community in Talang Kawo, Merangin Regency, regarding motor vehicle credit agreements with fiduciary guarantees makes them vulnerable to detrimental practices. This community service aims to empower the community by enhancing their understanding of their rights and obligations, particularly concerning fiduciary guarantee execution procedures following Constitutional Court Decision No. 18/PUU-XVII/2019. The method used was participatory legal counseling on March 26, 2025, with a descriptive qualitative approach. The activity's effectiveness was measured using pre-test and post-test instruments. The results showed a highly significant increase in legal understanding, with the average participant knowledge score rising from 38 to 82. It is concluded that the interactive counseling method successfully raised the community's legal awareness, equipping them with the knowledge to protect themselves from potential defaults and non-procedural executions.